2020
DOI: 10.1186/s12871-020-01015-9
|View full text |Cite
|
Sign up to set email alerts
|

The application of a neural network to predict hypotension and vasopressor requirements non-invasively in obstetric patients having spinal anesthesia for elective cesarean section (C/S)

Abstract: Background: Neural networks are increasingly used to assess physiological processes or pathologies, as well as to predict the increased likelihood of an impending medical crisis, such as hypotension. Method: We compared the capabilities of a single hidden layer neural network of 12 nodes to those of a discretefeature discrimination approach with the goal being to predict the likelihood of a given patient developing significant hypotension under spinal anesthesia when undergoing a Cesarean section (C/S). Physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Subarachnoid anesthesia has been extensively studied in the obstetric population [19], [20]. This historical cohort of patients for non-obstetric surgery describes a very high success rate with the use of the 29G pencil point needle without any reports of PDPH.…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid anesthesia has been extensively studied in the obstetric population [19], [20]. This historical cohort of patients for non-obstetric surgery describes a very high success rate with the use of the 29G pencil point needle without any reports of PDPH.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the random forest model showed the best performance, with an AUC of 0.842 ( 32 ). In another study authors compared the capabilities of a single hidden layer NN of 12 nodes to those of a discrete-feature discrimination approach in predicting significant hypotension under spinal anesthesia during cesarean section ( 33 ). The results presented suggested that a NN approach may be superior to a discrete feature quantification approach.…”
Section: Discussionmentioning
confidence: 99%
“…A common perioperative event is fluctuations in blood pressure, particularly hypotension, which can lead to serious complications, such as cardiovascular injury or even death. Several articles in this subcategory predicted hypotension before its occurrence to enable specialists to take necessary tasks to prevent it (27)(28)(29)(30)(31)(32)(33). Another crucial event is difficult laryngoscopy, defined as the inability to visualize part of the vocal cords during multiple laryngoscopy attempts by a trained anesthesiologist.…”
Section: Subcategory D1: Perioperativementioning
confidence: 99%